MID-WINTER WARMINGS IN THE SOUTHERN HEMISPHERE STRATOSPHERE IN 1988 - シオタニ, マサト; ヒロタ, イサム; クロイ, ケイコ; ヒラキ, トオル; SHIOTANI, Masato; HIROTA, Isamu; KUROI, Keiko; HIRAKI, Tooru (National Institute of Polar Research, 1991)
P(論文) An analysis was done of intense midwinter warmings which took place in the southern hemisphere stratosphere during August-September 1988. By using the southern hemispheric data set up to the 1 mb level provided by Japan Meteorological Agency, it is found that the 30 mb temperature increase over eastern Antarctica, about 60 K for 10 days from August 22 to September 1,is associated with the amplification of a quasi-stationary planetary wave of zonal wavenumber 1. The enhancement of wave 1 appears quasi-periodically with a times scale of about 2 weeks during the mid-winter of 1988. Clear evidence is presented to show that the quasi-periodic amplification of wave 1 is due to the wave-wave interaction between the quasi-stationary forced wave of wavenumber 1 and the eastward traveling wave of wavenumber 2. It is emphasized, therefore, that the mechanism of warming in this case is quite different from the transient vertical propagation of a planetary wave forced from below as observed in the northern hemisphere winter. departmental bulletin paper